A Practical guide to trade policy analysis (WTO & UNCTAD GenevaCH, 2011)
Focuses on quantitative economic methods and data sources for trade policy analysis. Combines detailed explanations of analytical techniques with a guide to the data necessary to undertake analysis. Includes tutorials in the form of exercises.
Keywords: TRADE POLICY